Thermal annealing and evolution of defects in neutron-irradiated cubic SiC - Bratus, V.Ya.; Melnyk, R.S.; Shanina, B.D.; Okulov, S.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
A careful study of neutron-irradiated cubic SiC crystals (3С-SiC(n)) has been performed using electron paramagnetic resonance (EPR) in the course of their thermal annealing within the 200…1100 °C temperature range. Several inherent temperatures have been found for annealing and transformations of primary defects in 3С-SiC(n) among which there are isolated negatively charged silicon vacancy VSi⁻, neutral divacancy (VSi–VC)⁰, negatively charged carbon vacancyantisite pair (VC–CSi)⁻ and neutral carbon (100) split interstitial (CC)C⁰. It has been shown that transformation of VSi⁻ into (VC–CSi)⁻ complex is among the mechanisms of silicon vacancy annealing. As it has been established on the basis of the observed hyperfine structure, the secondary T6 center is characterized by the fourfold silicon coordination and assigned to the spin S = 3/2 carbon vacancy-related pair defect. The symmetry reduction of the (VC–VSi)⁰ center is attributed to local rearrangements in the neighborhood of divacancy, and its intensity variations are assigned to changes of the Fermi-level position. Two defects with similar symmetry and close values of zero-field splitting constants D, which concentrations increase by a factor of ten after annealing at 900 °С, are tentatively attributed to the (100) split interstitial (CC)C⁰ and (NС)С⁰ pairs